Reduction effect of carbon markets: A case study of the Beijing-Tianjin-Hebei region of China - Weng, Zhixiong; Liu, Tingting; Cheng, Cuiyun (Frontiers in Environmental Science, 2022)
The carbon market is a crucial market-oriented tool in achieving carbon neutrality and has been adopted by many countries and regions. China has established a policy system covering eight carbon trading pilots since 2013 and has carried out a series of effective practices. However, differentiated characteristics of carbon trading pilots may significantly impact the development of the carbon market. This study took the Beijing-Tianjin-Hebei (BTH) region as the research sample and used a difference-in-differences approach to estimate the reduction effect of the carbon market. Our findings suggested that the carbon market in the BTH region effectively reduced its carbon intensity by 14.04%. Our estimations were robust after using a winsorization panel or establishing a new control group. Furthermore, the results also indicated that the carbon market’s effect on reducing carbon intensity differs across cities and shows an increasing trend yearly. Relevant recommendations for promoting carbon trading policies were proposed.